2011
DOI: 10.1038/nature09683
|View full text |Cite
|
Sign up to set email alerts
|

Vernier templating and synthesis of a 12-porphyrin nano-ring

Abstract: Templates are widely used to arrange molecular components so they can be covalently linked into complex molecules that are not readily accessible by classical synthetic methods. Nature uses sophisticated templates such as the ribosome, whereas chemists use simple ions or small molecules. But as we tackle the synthesis of larger targets, we require larger templates-which themselves become synthetically challenging. Here we show that Vernier complexes can solve this problem: if the number of binding sites on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
294
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 410 publications
(303 citation statements)
references
References 21 publications
5
294
0
4
Order By: Relevance
“…4 shows STM images of each cyclic polymer. In common with our previous work 5,25,26 the nanorings are preferentially adsorbed in configurations overlapping, or partially overlapping, terrace steps on the Au(111) surface, and the porphyrin macrocycles lie parallel to the substrate. In many images it is possible to resolve the porphyrin units providing confirmation of the degree of polymerisation, simply by counting the bright contrast features around the perimeter of a nanoring.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…4 shows STM images of each cyclic polymer. In common with our previous work 5,25,26 the nanorings are preferentially adsorbed in configurations overlapping, or partially overlapping, terrace steps on the Au(111) surface, and the porphyrin macrocycles lie parallel to the substrate. In many images it is possible to resolve the porphyrin units providing confirmation of the degree of polymerisation, simply by counting the bright contrast features around the perimeter of a nanoring.…”
Section: Resultsmentioning
confidence: 74%
“…Thus the contour length of a linear oligomer, or the perimeter of a nanoring, is Na, where N is the number of porphyrin repeat units. Previously we have shown that nanorings adsorbed on Au(111) exhibit flexibility [24][25][26] , and also that they can act as nanoscale traps for other adsorbed species, such as C 60 guest molecules 27 . However, in order for one nanoring to be adsorbed inside another, the dimensions of the nanoring must exceed a critical threshold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26] Due to the role in natural photosynthesis of related compounds porphyrin molecules have been extensively exploited for electron and energy transfer. [27][28][29][30] The light-harvesting properties of porphyrins 45 has led them to be considered as components in solar photovoltaic cells. [31][32][33][34] Currently, bulk hetero junctions (BHJ) are Scheme 1 Schematic representation of ZnTMPyP4 and CdTe systems 50 considered to show most promise for improved solar cell efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The UHV environment allows the preparation of clean surfaces prior to deposition and the in-situ application of high resolution scanning probe microscopy, electron spectroscopy and X-ray absorption techniques to understand interactions at the atomic and molecular scale. The combination of such techniques with UHV-compatible electrospray deposition has successfully been applied by the authors to the deposition of complex, fragile and non-volatile molecules on surfaces prepared in UHV including giant porphyrin nanorings, [23] single molecule magnets [24] and organometallic dye molecules [25]. Whilst these studies demonstrated the intact deposition of these complex molecules with retention of their chemical, electrical and magnetic properties the question remains if proteins deposited in this manner in vacuum retain their biological activity when returned to liquid environments of relevance to their application in a wide range of fields such as sensors, diagnostics and tissue engineering.…”
Section: Introductionmentioning
confidence: 99%